Intellectual Property Rights in Matrimonial Property - Natalia Vladimirovna Slesaryuk (Сибирское юридическое обозрение, 2011)
This article attempts to consider the extension of the joint property of spouses in intellectual property rights based on intellectual property in respect of which there are these rights. In particular, the author finds some unsettled property relations between spouses, in connection with which the autor proposes to amend the legislation.